Bacterial profile in children with early childhood caries - Sinta Dwi ARDIYANTINI; Hening Tjaturina PRAMESTİ; Meirina GARTIKA (Journal of Syiah Kuala Dentistry Society, 2022)
Early Childhood Caries (ECC) is the most common chronic infectious disease of childhood in the world, caused by the interaction of the host (oral cavity), substrate, microbes, and time. Bacteria as microbes that play a role in the formation of ECC have been widely studied. This study aims to determine the bacterial profile in children with ECC and to compare the oral microbial profiles in children with ECC and caries-free children (CF). Methods: This study uses a scoping review method. Article searches were performed on the PubMed, Science Direct, Cochrane, and Google Scholar databases, using the keyword and Boolean operator "(early childhood caries) AND (profile bacterial OR bacterial) AND (children)." The initial search obtained 1356 articles. All articles were then selected according to the inclusion and exclusion criteria using the PRISMA procedure to receive 14 articles. Results: Analysis of 14 articles showed that 11 articles reported that Streptococcus mutans had high levels of ECC in children. Other bacteria with lesser numbers were Provetella, Veillonella, S. wiggsae, S. sobrinus, Lactobacillus, Leptrotrichia shahii, and Leptrotrichia IK04. Neisseria, Streptococcus mitis, Streptococcus salivarius, and Leptotrichia buccalis were found in CF children. Other bacteria such as Hemophilus paraphrohaemolyticus HK411, Neisseria sicca 4320, Neisseria sp. oral clones AP132, Actinobacillus pleuro-pneumoniae MCCM 00189, and Streptococcus sp. ASCE06 oral clone was found in CF children but not in ECC children, while Lactobacillus sp C56 was found in half of ECC children and not in CF children. Conclusion: Streptococcus mutans levels in children with ECC are high, so they are assumed to be the main bacteria causing ECC. The bacterial profiles of ECC and CF children are different in species diversity. KEYWORDS: Early Childhood Caries, Bacterial, Children